Satellite Imagery and In-situ Data Overlay Approach for Fishery Zonation - Khairul Munadi; Fardhi Adria (Universitas Ahmad Dahlan, 2010)
Remote sensing technology is useful to give a better understanding about the earth’s characteristics. SeaWiFS (sea-viewing wide field-of-view sensor) is one of remote sensors used to observe global ocean phenomena. Previous studies showed that the distribution of chlorophyll-a in the ocean indicates the presence of fish. However, only a few studies tried to directly relate the chlorophyll-a distribution obtained through interpretation of satellite imagery to in-situ data of fish distribution. This paper investigates the relation between chlorophyll-a distribution and fish-capturing points in Aceh Province sea waters using overlay image analysis. The results are useful to identify the potential fishing ground in Aceh. The profile of chlorophyll-a concentration was derived from SeaWIFS satellite imagery and fish-capturing points data was obtained from the fisherman communities of Banda Aceh, starting from June to November 2008. The results show that the chlorophyll-a profile derived from satellite imagery has a positive relationship to fish-capturing point data. The most potential fish-capturing zone in Aceh sea waters is identified at 5-8º north latitude (N) and 96-99º east longitude (E).